PENGARUH HUKUM PIDANA INTERNASIONAL TERHADAP HUKUM PIDANA NASIONAL - Wahyu Wahyu Wahyu (Belom Bahadat, 2019)
The relationship between international criminal law and national criminal law is a complementary relationship. His relationship can be seen from the many international legal conventions which are also part of international criminal law adopted in national criminal law.